Pengembangan Sistem IoT untuk Pemantuan Kehadiran Mahasiswa Berbasis Sensor Wajah dan RFID di Kampus Menggunakan Metode Radio Frequency Identification(RFID) (International Forum of Researchers and Lecturers, 2024)
Student attendance monitoring is a crucial aspect in education to ensure that students are present in classes and to minimize the potential for fraud. In this study, we developed an Internet of Things (IoT) system to monitor student attendance on campus using two main technologies: facial recognition and Radio Frequency Identification (RFID). The system utilizes RFID technology to identify students through RFID cards issued to each student, as well as facial recognition sensors for additional verification to enhance accuracy and security. This system is designed to provide convenience, security, and efficiency in the attendance process on campus.